Epidemiology of sport-related concussion rates in female contact/collision sport: a systematic review. Issue 3 (20th September 2022) - Walshe, Ayrton; Daly, Ed; Ryan, Lisa
Abstract : Objectives: To determine sport-related concussion (SRC) incidence rates in female contact/collision sport. Design: Systematic review following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Data sources: Four databases (PubMed, SportsDiscus, Web of Science, CINAHL) were searched for data from 2012 to 2021. Eligibility criteria: Studies reporting SRC incidence rates or the number of concussions and athletic exposures (AEs) per 1000 participating events or hours in healthy female contact and collision sport athletes of any age were included. Results: The search yielded 8438 non-duplicate articles. Following screening, 19 were included in the analysis (median quality score=70%), with 8 reporting match or training incidence rates. Studies were primarily from US high school and collegiate populations; data are reported for eight sports. Rugby union reported the highest match SRC rates (8.2–16.11 per 1000 AE hours), followed by Gaelic football (5.21 per 1000 AE hours) and soccer (2.08–4.04 per 1000 AE events). Where available, match SRC rates were substantially higher than training and overall SRC rates. Conclusion: Female sports such as rugby union, Gaelic football and soccer present the highest risk for SRCs within the available data. Previous research indicates a potentially greater injury burden for female athletes experiencing SRCs than their male counterparts. Thus, future research should analyse concussion knowledge and return-to-play protocols in these sports. Future research should also prioritise exploration of the gap in SRC rates within amateur sports, and data should be presented specifically in the context of athletic exposures (match vs training). Trial registration number: CRD42021281569.